Booklet development based on research identification of fiddler crab (Uca spp.) diversity in mangrove ecosystem - Ajizatunnisa Ajizatunnisa; Sri Wahyuni; Lud Waluyo; Fuad Jaya Miharja (JPBI (Jurnal Pendidikan Biologi Indonesia), 2018)
The purpose of this development study is to develop research-based booklet for the identification of fiddler crab (Uca spp.) diversity. Some people do not yet know the ecological benefits of fiddler crabs. This is apparent when some people take fiddler crabs to serve as decorative crabs. The product specifications expected in the development of this medium are booklets. Therefore, it takes a companion learning media that can lead the local community to implement self-learning in the form of booklet because their interest of reading is very less, especially when reading a book that is colorless and has a lot of words. Booklet that is packed with interesting and accompanied by pictures is an alternative solution. The development method used in the research is Exploration, Explanation, and Evaluate (3E) model. The research was conducted by developing the research result into a booklet based on the diversity of fiddler crabs in mangrove ecosystem. The booklet validation consists of two lecturers from the Department of Biology Education at the University of Muhammadiyah Malang which is a material expert and learning media expert. The result of this research is booklet very valid with the percentage of material expert validity 81.25% and learning media expert 95.13%.